problem was to prove that ∑(n=0 to n=∞) t^2n ∫(-1 to 1)P^2(n)(x)dx=∫(-1 to 1) (dx ÷(1-2xt+t²)) = (1÷t)(log(1+t) ÷log(1-t))
upto this i followed but after that last step the book which i am refering gives answer =2÷(2n+1)
can u just help me how to come to that answer.. plz give me steps to follow..
The first thing is that has to formatted in a way that can be read. Do you know how to use latex?
First of all what is P^2(n)(x)? The Legendre polynomials? Did I interpret your problem correctly in my latex?
If it ain't broke, fix it until it is.